Kajian Kebutuhan Tenaga Kerja Proyek Bangunan Gedung Menggunakan AHSP 2016 - Ria Zulfiati; Annisaa Dwiretnani; Ilham Iman Patra (Universitas Batanghari Jambi, 2023)
Construction work can run well if it is supported by good human resource selection factors. If a job without the support of good human resources in terms of quality and productivity, the results obtained will not be optimal and will not be satisfactory. Not only that, the inappropriate use of human resources can cause huge losses to construction projects. To regulate or manage the use of human resources to be more efficient, the contractor must know the level of productivity of each worker. This study aims to determine the coefficient of analysis of the unit price of labor in the field and SNI 2016 and to compare the coefficient of analysis of the unit price in the field and SNI 2016. The research was conducted on a rehabilitation project for facilities and infrastructure in the Sungai Gelam campground area, Jambi province. The data used consists of primary data, namely interview data and secondary data, which consists of work drawings, reports, analysis of work unit prices and RAB. The data obtained were analyzed using the Time & Motion Study method. From the results of the analysis, the results of the evaluation of the need for labor in the field were based on SNI, namely for the coefficient of labor in the field for plastering Ad 1:4 work, it was 0.1411 OH, while based on SNI it was obtained. 0.2550 OH. for the coefficient of labor in the field on the work of Stone Pair 1 stone Ad 1:4 it gets 0.3025 OH while based on SNI it gets 0.4250 OH. Based on the calculation, the coefficient in the field is smaller than the coefficient of the analysis of the SNI work unit price.